2021
DOI: 10.4085/1062-6050-0696.20
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Based Review of the Pathophysiology, Treatment, and Prevention of Exercise-Associated Muscle Cramps

Abstract: Exercise-associated muscle cramps (EAMC) are common and frustrating for athletes and the physically active. We critically-appraised the EAMC literature to provide evidence-based treatment and prevention recommendations. While the pathophysiology of EAMC appears controversial, recent evidence suggests EAMC are due to a confluence of unique intrinsic and extrinsic factors rather than a singular etiology. The treatment of acute EAMC continues to include self-application or clinician-guided gentle static stretchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 59 publications
0
7
0
1
Order By: Relevance
“…The Institute of Medicine80 has recognised that public health recommendations to limit sodium ingestion should not be applied to individuals with elevated sweat loss due to exercising in the heat. While exercise-associated muscle cramps are mainly due to premature muscle fatigue121 and not salt depletion,122 exercise in the heat may also promote muscle cramping in some athletes,13 probably when the sodium deficit reach 20%–30% of the exchangeable sodium pool 123. Thus, most athletes should include a solution with 0.5–0.7 g/L of sodium in their hydration plan when exercising >1 hour 111 124 125.…”
Section: Section 2: Recommendations For Risk Mitigation By the Athletesmentioning
confidence: 99%
“…The Institute of Medicine80 has recognised that public health recommendations to limit sodium ingestion should not be applied to individuals with elevated sweat loss due to exercising in the heat. While exercise-associated muscle cramps are mainly due to premature muscle fatigue121 and not salt depletion,122 exercise in the heat may also promote muscle cramping in some athletes,13 probably when the sodium deficit reach 20%–30% of the exchangeable sodium pool 123. Thus, most athletes should include a solution with 0.5–0.7 g/L of sodium in their hydration plan when exercising >1 hour 111 124 125.…”
Section: Section 2: Recommendations For Risk Mitigation By the Athletesmentioning
confidence: 99%
“…In general, the results demonstrate that rehydration with Zamzam water following significant dehydration may help to maintain or even improve cardiorespiratory fitness. Rehydration with fluid following the loss of 2% or more of body weight could help to prevent a decline in sports performance [9,[22][23][24][25]. Several studies have examined the effect of exercise-induced dehydration on cardiorespiratory fitness [7,26].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the results of the study demonstrated that rehydrating with Zamzam water following significant dehydration may help to maintain or even improve cardiorespiratory fitness. Rehydration with fluid following 2% or more of losing weight could help to maintain or eliminate the decline of sports performance [7,[20][21][22][23]. A number of studies examined the effect of exercise-induced dehydration on cardiorespiratory fitness [24,25].…”
Section: Discussionmentioning
confidence: 99%